The Old Testament Babylonian exile : a socio-political study - Bookholane, L J (Department of Religious Studies, 2023)
This study is a materialist literary analysis of Deuteronomistic History. with particular reference to the Elijah-cycle which culminates in the Naboth Episode its appropriation by the oppressed in their situation and experience of oppression in contemporary societies. The materialist literary criticism which is adopted in theses requires an approach to the Bible which views it as a text and at the same time a social activity. that the contemporary oppressed must inquire into the social class of the writers of the Deuteronomistic history in order misappropriate the Naboth isode